Late Ediacaran to Early Cambrian stratigraphic correlation and its geological implications in the northwestern Sichuan Basin: insights from phosphorus, isotopes, and small shelly fossils - Li, Wenzheng; Zhang, Jianyong; Zhu, Xinjian; Wang, Yongxiao; Tian, Xingwang; Fu, Xiaodong; Jiang, Hua; Zhong, Yuan; Liu, Shugen; Li, Rong; Pan, Bing; Deng, Bin (Frontiers in Earth Science, 2024)
Elements, isotopes and small shelly fossils characteristics were investigated to divide the stratigraphy of late Ediacaran to early Cambrian and discuss its geological implication in the northwestern Sichuan Basin. The results reveal that small shelly fossils can be detected in the high phosphorous section mainly ranging from 2% to 8%, suggesting that this interval belong to the early Cambrian, which is also consistent with the carbon isotopic composition results. In addition, the Early Cambrian are denudated in the Sichuan Basin due to tectonic movement, some isotopes and small shell fossils characteristics are different from those in other basins. It can be proposed that P content can support the recognition of lithological boundaries, and the high phosphorus content can be used as a reference to identify the top and bottom boundaries of the Maidiping Formation in the study area. According to the elemental compositions in the Ediacaran Dengying Formation, the variation of Si, Al, Fe, K contents are similar in platform area and rift area, suggesting that the third member and fourth member of Dengying Formation are also developed in the Deyang-Anyue Rift. The results suggest that both the Deng-4 member and Maidiping Formation feature contemporaneous difference facies in the northwestern Sichuan Basin. The strata consist of shale intercalated with thin carbonate rock deposits in the Deyang-Anyue Rift, while carbonate rock deposits in the platform. Deyang-Anyue Rift expand gradually in the late Ediacaran, and eventually filled in the early Cambrian. The data exhibited in this study illustrates that elemental compositions, isotopes, and small shell fossils can be combined to correlate the late Ediacaran to early Cambrian strata, and provide new evidence for Deyang-Anyue Rift evolution. The results offer some new insights for deep oil and gas exploration in the Sichuan Basin and for the tectonic-depositional-environmentalbiological synergistic evolution in the late Ediacaran to early Cambrian transition.